1996
DOI: 10.1002/cber.19961290207
|View full text |Cite
|
Sign up to set email alerts
|

2,5‐Dihydro‐1,2,5‐azoniasilaboratole Derivatives – Useful Starting Materials in Heterocyclic Synthesis

Abstract: 1-Alkynyl(diethy1amino)dimethylsilanes [C=CR: R = Me (la), nBu (lb), SiMe, ( l c ) ] react with triethylborane stereoselectively by 1,l-ethyloboration to give the alkenes with the boryl and silyl group in cis-positions at the C=C bond. Owing to the strongly intramolecular coordinative N-B bond, these products are 2,5-dihydro-1,2,5-azoniasilaboratoles (2a-c). Protic reagents such as azoles (indole, pyrazole, imidazole, triazole, indazole, benzotriazole) react with 2 to give diethylamine and the respective N-azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…8 Alkenes bearing organometallic substituents at the C C bond are attractive reagents for further transformations. Various methods have recently been reported for the preparation of alkenes with boryl and silyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…8 Alkenes bearing organometallic substituents at the C C bond are attractive reagents for further transformations. Various methods have recently been reported for the preparation of alkenes with boryl and silyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…The intramolecular interaction between boryl groups and heteroatom-functionalized silyl groups has been precisely investigated by Wrackmeyer et al with multinuclear NMR spectroscopy . They prepared a number of compounds in which a heteroatom-functionalized silyl group and a boryl group were bonded to an alkene skeleton in a cis fashion and revealed that such compounds formed unique silicon−heteroatom−boron bridges.…”
mentioning
confidence: 99%
“…Data for this compound matched that from the literature. 6 In an oven dried a 35 mL 1-neck round-bottom flask was combined N,N-diethyl-1,1dimethyl-1-(1-propynyl)silanamine (6.54 g, 38.6 mmol, 1.0 equiv), methanol (2.35 mL, 57.9 mmol, 1.5 equiv) and Et 2 O (20 mL). This reaction was stirred for 1 h at room temperature and then purified by fractional distillation to afford 3.26 g (66%) of a clear, colorless liquid.…”
mentioning
confidence: 99%